INTERACTIVE TOOLS FOR LINEAR ALGEBRA: GEOUNIUD - Lepellere, Maria Antonietta; Zucconi, Francesco; Al Asbahi, Nizar Salahi; Carminati, Alberto (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
GeoUniud is a user-friendly platform built-in interactive tutors which allow students to investigate specific tasks by selecting their own input values and working through a problem in a step-by-step fashion together with immediate feedback at each step. Lessons and exercises are stored and organized with a careful use of randomized controlled contents as exercises, geometrical pictures and abstract reasoning. The lessons are augmented by a virtually infinite collection of examples, and by interactive representations of concepts. As example we show the design of two interactive tools about linear transformation and change of basis in order to develop students’ sense-making in a dynamic geometry environment (DGE) within the perspective of semiotic mediation.